Permanence : a novel - Mackintosh, Sophie (Avid Reader Press, 2026)
"From one of Granta's Best Young British Novelists, the critically acclaimed author of the speculative dreamscapes The Water Cure andBlue Ticket, comes the story of a clandestine affair and an alternate city seemingly designed to foster it... Clara and Francis are in love, but nobody knows it. For months they have been stealing away from their respective lives, leaving no trace of their relationship behind. Their time together is always excruciatingly sweet and all too short. Until one day they wake up in an apartment neither of them recognizes, with no memory of how they got there. They find themselves in a new, unnamed city, a self-contained sanctuary where adulterers live openly as couples. Here there are fountains and old town squares and perfect cafes with checkered tablecloths. Ripe fruits wait on the counter each morning, invisible threads bind each lover to the other, and their primary responsibility is to enjoy one another. Contact with the real world is impossible and the city's whims are mysterious-but now those stolen afternoons never have to end. How muchwould you sacrifice for a life you never thought possible? And how long can you stay in paradise before the cracks start to show? An exploration of desire, novelty, and choice, Permanence explores the tantalizing quandary of what, if anything, can withstand the daily toll of "forever""--